FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPEMILIKAN JAMBAN SEHAT DI WILAYAH KERJA PUSKESMAS LAMPAHAN KECAMATAN TIMANG GAJAH KABUPATEN BENER MERIAH - Juhra, Fitri; Elyarianti; Alamsyah, Sanjaya (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACT This study is a quantitative research with a cross-sectional approach. The population in this study consists of heads of households who do not own a family latrine, totaling 300 respondents. The sample size is 75 respondents, selected using Accidental Sampling. The research instrument used a questionnaire, and data analysis was performed using univariate and bivariate methods with the chi-square test. The study findings reveal that the level of knowledge about family latrines is low, with 53.5% or 40 respondents showing insufficient knowledge. The attitude towards family latrines is also poor, with 53.5% or 40 respondents reflecting negative attitudes. The income level related to family latrines is moderate, with 62.7% or 47 respondents falling into this category. Family latrine ownership is reported to be poor, with 76.0% or 57 respondents lacking adequate facilities. Based on the chi-square test results, the p-value for the knowledge variable is (0.03) ≤ (0.05), indicating that the null hypothesis (Ha) is accepted and there is no significant relationship between knowledge and latrine ownership. For attitudes, the p-value is (0.03) ≤ (0.05), indicating a significant relationship between attitudes and latrine ownership. For income, the p-value is (0.03) ≤ (0.05), suggesting a significant relationship between income and latrine ownership. To improve public health, it is essential to enhance understanding and awareness of the importance of having a family latrine. This can prevent the practice of open defecation and discourage the habit of disposing waste in rivers or other areas without septic tanks, thus avoiding environmental contamination and promoting healthier living conditions. Keywords : Knowledge, Attitude, Income